A new genus and species of Ortaliini (Coleoptera Coccinellidae: Ortaliinae) from Palawan, Philippines - Adorada, Jessamyn D. Recuenco (2011)
Elnidortalia, n. gen., and a new species E. bipunctata n. sp. from Palawan are described and illustrated. Key to the genera of Philippine Ortaliini is also included.
Keywords: Ladybugs; Ladybugs -- Identification